Correlations between iodine status and the risk of thyroid nodules, a systematic review and dose–response meta-analysis - Lu, Changbo; Dong, He; Shi, Peishen; Dong, Weichen; Wen, Xinxin; Gao, Qiuming (Frontiers in Endocrinology, 2026)
BackgroundThe global incidence of thyroid nodules is rising substantially. The correlation between excessive iodine intake and an elevated risk of thyroid nodules remains a subject of debate.ObjectiveTo evaluate the categorical and quantitative dose-response associations between iodine status levels and the risk of thyroid nodules.MethodsWe systematically searched PubMed, Web of science, Embase, Cochrane Library and Scopus for studies published before December 2025 that investigated the association between iodine status and thyroid nodules, without language restrictions. The categorical association was assessed by pooling odds ratios (ORs) for thyroid nodules across different iodine status categories, using the adequate category as the reference. The continuous dose-response association was evaluated using random-effects generalized least squares spline models. The primary outcome was the prevalence of thyroid nodules at different iodine status statuses.ResultsThis meta-analysis included 25 cross-sectional studies comprising 54621 participants (57.7% women) and 13569 thyroid nodule events. In categorical analyses, participants in the iodine deficiency (median urinary iodine concentration [UIC]: 50 μg/L) showed higher odds of thyroid nodules (OR = 1.28, 95%CI=1.09-1.50) compared to the adequate iodine category (median UIC, 150 μg/L). No significant association was found for both the more-than-adequate iodine (median UIC, 250 μg/L) category and excessive iodine (median UIC, 350 μg/L) categories (OR = 1.02, 95% CI = 0.93-1.11; OR = 1.13, 95%CI=0.98-1.30, respectively). Nine studies reporting continuous UIC outcomes, the mean difference (MD) between participants with and without nodules was 4.11 (95% CI, 2.51 to 5.71, P < 0.01). Continuous dose-response analysis revealed a significant U-shaped nonlinear correlation (P for nonlinearity < 0.001), with increased risks at both deficient and excessive iodine levels. These associations remained consistent in analyses by unadjusted variables of sex, age and BMI. Further analysis stratified by geographical factors also revealed similar correlation tendency.ConclusionsThe relationship between iodine intake and thyroid nodule risk follows a U-shaped, nonlinear pattern, where both deficiency and excess are associated with increased risks. More than adequate iodine intake showed a trend toward a lower prevalence of thyroid nodules. However, this observation should be interpreted with caution due to wide confidence intervals, heterogeneity, and potential residual confounding.Systematic Review RegistrationPROSPERO, https://www.crd.york.ac.uk/PROSPERO/view/CRD420251236621, identifier CRD420251236621.